Hallucinations and Strong Priors. Issue 2 (February 2019) - Corlett, Philip R.; Horga, Guillermo; Fletcher, Paul C.; Alderson-Day, Ben; Schmack, Katharina; Powers, Albert R.
Abstract : Hallucinations, perceptions in the absence of objectively identifiable stimuli, illustrate the constructive nature of perception. Here, we highlight the role of prior beliefs as a critical elicitor of hallucinations. Recent empirical work from independent laboratories shows strong, overly precise priors can engender hallucinations in healthy subjects and that individuals who hallucinate in the real world are more susceptible to these laboratory phenomena. We consider these observations in light of work demonstrating apparently weak, or imprecise, priors in psychosis. Appreciating the interactions within and between hierarchies of inference can reconcile this apparent disconnect. Data from neural networks, human behavior, and neuroimaging support this contention. This work underlines the continuum from normal to aberrant perception, encouraging a more empathic approach to clinical hallucinations. Highlights: Recent data establish a role for strong prior beliefs in the genesis of hallucinations. These data are difficult to reconcile with aberrant inner-speech theories, in which 'weaker' predictions about the potential consequences of one's own inner speech drive an inference that speech is emanating from an agent external to oneself. In the predictive-coding view, this failure of self-prediction renders the consequences of one's inner speech surprising. The prediction errors induced are explained away by the strong higher-level priors identified in recent work. The presence and contents of hallucinations can be understood in terms of learning, inference, and a reliability-based trade-off between internal and external information sources, biased toward high-level priors. If priors divorce perception from sensation somewhat, the distinction between hallucination and perception becomes less clear. We hope this explanation renders hallucinations more understandable and less stigmatizing.